Memotret Agama Adam: Studi Kasus pada Komunitas Samin - Rosyid, Mohammad (Jurnal Orientasi Baru, 2014)
Interreligious tolerance in this nation may be achieved through the understanding of local religions’ concept on tolerance, which is practiced by indigenous community. The understanding is expected to gradually reduce religious prejudice. Once, the understanding of other religion is reached, religious difference will not triggered conflict among people from different religious background, in contrary the difference will be treated as a gift of God. This paper attempts to open Pandora box of Samin community perceived to be atheist. Understanding God in the religion of Adam (Samin people’s religion) is the foundation of awareness that Samin people also believe in God and perform their own religious obligations, such as pray and fasting. Meanwhile, the government categorizes the religion of Adam as belief system, not religion. There is difference between belief system and religion.